Les acteurs publics locaux et l’écologisation de l’agriculture - Pascale Scheromm; Annabel Rixen; Lucette Laurens; Christophe-Toussaint Soulard (Développement Durable et Territoires)
How does agroecology, as a political and institutional project, take shape at the local scale? In this article, we analyze in which objectives and how local public actors implement agroecological initiatives. We draw on four initiatives developed in periurban municipalities of South of France. Our results highlight the implication of non agricultural local actors in the emergence of these initiatives, in particular elected representatives in particular elected representatives and environmental managers, in connection with associations of the civil society and environmental managers. These results point out a plural process of territorialisation of the agroecology and its effects on the greening of the agricultural practices.